Monitoring the energy of the metal ion-content plasma-assisted deposition and its implication for bacterial inactivation - Rtimi, Sami; Nadtochenko, Victor; Khmel, Inessa; Konstantinidis, Stéphanos; Britun, Nikolay; Kiwi, John (Applied surface science, 2019)
[Display omitted] •Differentiated effect of the plasma energy used to deposit Cu on PES is studied.•Distinct bacterial inactivation kinetics of E. coli were observed on Cu-PES samples.•The amounts of ions generated in the plasma phase were identified by mass spectrometry.•The effects of extracellular Cu-NPs and the intracellular Cu-ionic were investigated.•Bacterial inactivation kinetics were studied on E. coli and porinless E. coli. Cu-polyester (Cu-PES) was sputtered by high power impulse magnetron sputtering (HIPIMS) and by low energy direct current magnetron sputtering (DCMS). The total amount and distribution of the Ar+, Cu+ and Cu2+ ions were determined as well as the bacterial inactivation kinetics mediated by DCMS and HIPIMS samples. The separation of extracellular and intracellular processes leading to bacterial inactivation was assessed on normal and genetically modified E. coli.